2015
DOI: 10.1002/2015jd023425
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and potential sources of atmospheric mercury at a subtropical near‐coastal site in East China

Abstract: To evaluate the impact of regional mercury (Hg) emissions and understand possible source regions of atmospheric Hg in Eastern China, 2 year observation for speciated atmospheric Hg was conducted at the Dameishan Atmospheric Observatory, a mountain site near the east coast of China. The observed concentration of total gaseous Hg (TGM) was 3.3 ± 1.4 ng m À3 . During the sampling period, gaseous oxidized Hg and particulate bound Hg were 6.7 ± 4.3 pg m À3 and 180 ± 110 pg m À3 in winter and 5.9 ± 3.4 pg m À3 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 55 publications
5
19
0
3
Order By: Relevance
“…Journal of Geophysical Research: Atmospheres (Figure 4), consistent with the 2-25 pg/m 3 GOM observed in these regions (Chand et al, 2008;Fu, Zhang, Yu, et al, 2015;Yu et al, 2015). The simulated PBM concentration is 5-10 times higher than the GOM concentration (Figures 3 and 4).…”
Section: 1029/2018jd028350supporting
confidence: 80%
“…Journal of Geophysical Research: Atmospheres (Figure 4), consistent with the 2-25 pg/m 3 GOM observed in these regions (Chand et al, 2008;Fu, Zhang, Yu, et al, 2015;Yu et al, 2015). The simulated PBM concentration is 5-10 times higher than the GOM concentration (Figures 3 and 4).…”
Section: 1029/2018jd028350supporting
confidence: 80%
“…The predominant wind direction during the wet season is from the east and the site mainly receives clean marine air masses. During the dry season, the predominant wind direction changes to from the northwest, which enhances the transport of air pollutants from northern and eastern China to the sampling site (Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Simian, Ma et al, 2016) were all located in mountaintop forests. Although the observations at some of these sites showed elevated PBM concentrations (mean: 31-154 pg m −3 ) (Fu et al, 2015b;Yu et al, 2015), washout of PBM below cloud was not expected to contribute significantly to Hg in precipitation because of low cloud base heights (Ray et al, 2006). In addition, observations of GOM at high-altitude sites in China (i.e., MWLG, MAL, and Shangri-La) showed mean concentrations of 2-8 pg m −3 (Fu et al, 2012a, b;, significantly lower than those (20-87 pg m −3 ) measured at highaltitude sites in North America and Europe (Swartzendruber et al, 2006;Fain et al, 2009;Weiss-Penzias et al, 2009;Fu et al, 2016).…”
Section: Comparison With Observations In Other Regions Worldwidementioning
confidence: 99%
See 1 more Smart Citation
“…During the non-ISM period (from October to April), the dry and cold air masses from Siberia and central Asia move through mainland China into the Pacific Ocean via the westerlies (Hsu, 2005;Fan et al, 2013;Yu et al, 2015). The monsoonal wind changes play an important role in the transport of regional Hg emissions in southeast and east Asia (Sheu et al, 2010;Tseng et al, 2012;Lee et al, 2016).…”
mentioning
confidence: 99%